Pseudo elliptic dual-band filters based on ring structures / Zuhani Ismail Khan - Ismail Khan, Zuhani (Institute of Graduate Studies, UiTM, 2015)
In recent years, wireless transmission via high frequency electromagnetic wave has been given a lot of attention from various industries due to the emergence of new applications and new technologies. One of the most recent and interesting evolution in the wireless communications area is the trend toward the integration of multiple functions into a wireless device that can be used anywhere. One of the main components in the communication system is the microwave filter. The performance of the device is defined in terms of its transmission loss, circuit size and response selectivity. Dual-band filters are seen as the solution for circuit size reduction in a dual-channel communication system…